Research study on developing an optimal system for agricultural machinery maintenance and repair - L, Lkhagvasuren; J, Tumen; G, Gantulga (Mongolian Journal of Agricultural Sciences, 2019)
In this paper presented the results of research studies on developing an optimal system of “agriculture tractor –– mobile service and repair unit” using a mathematical model of Queuing Theory, by applying a criteria of minimal loss of agricultural tractor and other machineries exploitation. An applicability of this system for was analyzed according to the Marcov theory and theory of probability. This mathematical model for optimizing agricultural machinery maintenance and repair system has been tested and proven for practical application at “Agromachtech” LLC, a distributer company of YTO International in Mongolia. Within this study a comparative analysis has conducted for some of the maintenance and service parameters of this “agriculture tractor –– mobile service and repair unit” system developed by the authors. An optimization made for the numbers of maintenance and service groups (channels). Хөдөө аж ахуйн машин-тракторын засвар, техникийн үйлчилгээний оновчтой тогтолцоог тогтоох судалгаа Хураангуй: Уг эрдэм шинжилгээний өгүүлэлд “Трактор & засвар, үйлчилгээний явуулын нэгж” тогтолцоог оновчлох асуудлыг Марковын онолд тулгуурлан, магадлагаат шинж төлөв бүхий математик загвар болон сул зогсолтын хамгийн бага алдагдал шалгуурыг ашиглан гүйцэтгэсэн судалгааны ажлын үр дүнг үзүүлсэн болно. Судалгааны ажлын хүрээнд бидний боловсруулсан онол аргазүйн үндэслэлийг үйлдвэрлэлд ашиглаж болохыг YTO фирмийн тракторын диллер “Агромаштех” ХХК-ийн засвар, үйлчилгээний явуулын автомашины үйл ажиллагааны жишээн дээр туршилт, тооцоогоор батлав. Түлхүүр үг: Засвар-техникийн үйлчилгээ, Нийтийн үйлчилгээний онол, Трактор, Засвар үйлчилгээний явуулын нэгж